Rehmanniae Radix, an Effective Treatment for Patients with Various Inflammatory and Metabolic Diseases: Results from a Review of Korean Publications - Seok-hee Kim; Tae-han Yook; Jong-uk Kim (Korean Pharmacopuncture Institute, 2017)
Objectives: This study was a review of the literature published on the efficacy of Rehmanniae Radix to obtain information to provide both a foundation for its clinical use and directions for future studies. Methods: This study selected 30 publications registered to databases or published in Korea by March 13, 2017, by searching electronic journal databases, i.e., NDSL, OASIS, RISS, and KISS, in order to review the efficacy of Rehmanniae Radix. The search was conducted using the keywords '生地黃', '鮮地黃', 'Rehmannia Glutinosa', and 'Rehmanniae Radix', and the search results were compiled and analyzed. Results: The selected publications included antioxidant effects (12 publications), data involving blood glucose reduction (4 publications), effects on the autonomic nervous system (3 publications), and effects on the human body (11 publications). Conclusion: The results of this